Child Neglect inside Families: A Theoretical Study of the Causes and Consequences - Mahir Abdulwahid Aziz; Bekhal Qader Sofi Mohammed (QALAAI ZANIST JOURNAL, 2024)
This theoretical study deals with the most vital issue facing children in the modern world. It focuses on child neglect inside families and how children are affected by it. The objective of this study is to discuss the causes and consequences of the child neglect phenomenon. Methodologically, this study applied the explanatory and descriptive analytic approaches, which involve providing a description of the cause and consequences of the phenomenon. Therefore, this study uses a literature review and text analysis. This study consists of eight sections. The first section provides the introduction, study problems, and significance of this study. The second section covers the historical background of child neglect. The third section, deals with a review of the literature as well as conceptualizing child neglect, and section four covers various forms of child neglect, along with their causes and consequences. The fifth section included methodology and the study hypothesis. The study’s outcomes and conclusions are covered in Section six. Section seven offers the study discussions, and the conclusion of the study is presented in Section eight. In conclusion, the socialization process has a negative relationship with child neglect, in addition, there is a correlation between the economic status of family and child physical neglect, this study also discovered that child neglect is heavily influenced by family educational background and general knowledge in daily social life.